Dermatophytic melanonychia: A case series of an increasing disease. Issue 5 (16th January 2021) - Starace, Michela; Ambrogio, Francesca; Bruni, Francesca; Piraccini, Bianca Maria; Alessandrini, Aurora
Abstract: Background: Melanonychia refers to brown‐black colour pigmentation due to melanin or not‐melanin deposition in the nail plate. Onychoscopy allows to distinguish if the pigmentation is due by melanin or not. The main causes of non‐melanic pigmentation are subungual haematoma and pigmented onychomycosis. Fungal melanonychia (FM) is rare and may present as diffuse or longitudinal pigmentation. Differential diagnosis includes melanic activation, such as ethnic‐type nail pigmentation or frictional melanonychia, but also versus melanic proliferation, such as nevus or nail melanoma. Fungal melanonychia can be due to a colonisation by fungi with black variant or by melanin activation due to inflammation of fungal invasion. Objectives: The aim of paper is to increase clinical and dermoscopic knowledge of this increasingly frequent disease. Methods: In this retrospective observational study, twenty patients with dermatophytic melanonychia were collected, with available clinical and dermoscopic pictures. The diagnosis of dermatophytic melanonychia was made based on clinical manifestation and mycological examination. KOH smear was performed in all cases. For each patient, clinical data included: age, gender, type of melanonychia and involved fingers. Results: This study aimed to show increased incidence of dermatophytic melanonychia and its correct management. In addition, we reviewed our collected cases and described the clinical and dermoscopic features of dermatophytic melanonychia. Conclusions: The results of this study showed that physicians should keep in mind the diagnosis of this increasing disease, and that it cannot be performed relying only on clinical grounds. We would like to highlight the importance of tools as KOH examination, culture and dermoscopy.